Managing disruptive family members. (2nd July 2019) - Pendlebury, Gabrielle
Abstract : How should confiict with a patient's relative be managed? Dr Gabrielle Pendlebury, Medicolegal Consultant at Medical Protection has some advice for practice managers about the steps to follow to resolve the situation